Pericervical Injection of 99mTc-Nanocolloid Is Superior to Peritumoral Injection for Sentinel Lymph Node Detection of Endometrial Cancer in SPECT/CT. (December 2016) - Sahbai, Samine; Taran, Florin-Andrei; Fiz, Francesco; Staebler, Annette; Becker, Sven; Solomayer, Erich; Wallwiener, Diethelm; la Fougère, Christian; Brucker, Sara; Dittmann, Helmut
Abstract : Purpose: Scintigraphic mapping of sentinel lymph node (SLN) is increasingly performed in patients with endometrial carcinoma although its routine clinical use is still under investigation. The purpose of this study was to compare preoperative SLN detection by means of SPECT/CT using pericervical (PC) versus hysteroscopic peritumoral (PT) injection. Patients and Methods: One hundred forty consecutive patients with endometrial carcinoma who underwent surgery and preoperative SLN SPECT/CT with 99m Tc-nanocolloid were included. Seventy women received hysteroscopic injection at 3 PT sites, and 70 women received PC injection at 3-, 6-, 9-, and 12-o'clock positions. Each patient underwent SPECT/CT followed by modified radical hysterectomy with lymphadenectomy on the day after. Histopathological results were collected for validation. Results: Three hundred thirty-four SLNs were detected by SPECT/CT in 106 patients (mean, 3.15; range, 1–9). The detection rate after PC nanocolloid injection was 83% versus 69% after PT injection (Pearson χ 2 test, P = 0.049). However, PT application resulted in a higher rate of para-aortic SLNs (PC: 60% vs PT: 38% of positive scans, P = 0.02). SPECT/CT yielded an overall sensitivity of 70% for the SLN detection in women with lymph node metastases with 3 false-negative cases. Failure to detect SLN was mostly associated with uptake in the reticuloendothelial system (liver, spleen, and bone marrow) or peritoneal diffusion in both cohorts. Negative scans after PT application often showed a minor to even failing injection depot. Conclusions: Pericervical injection leads to a significantly better detection rate of SLN on SPECT/CT while reducing invasiveness of the injection procedure. Failure to detect SLN seems to be associated with major venous drainage.